2022
DOI: 10.1175/jtech-d-21-0088.1
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Finescale Strain Estimates of Turbulent Kinetic Energy Dissipation by Frontal Physics

Abstract: Finescale strain parameterization (hereafter, FSP) of turbulent kinetic energy dissipation rate has become a widely used method for observing ocean mixing, solving a coverage problem where direct turbulence measurements are absent but CTD profiles are available. This method can offer significant value, but there are limitations in its broad application to the global ocean. FSP often fails to produce reliable results in frontal zones where temperature-salinity (T/S) intrusive features contaminate the CTD strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…For instance, Liang et al (2021) reported an increase in R ω with depth based on observations conducted in the western Pacific, and established a relationship of R ω (z) = 10 z/b , where b = 2,500 m and z represents water depth. Ferris et al (2022) focused on the Drake Passage region and proposed a depth-dependent parameterization of R ω (z) = 6.5 + 3.5 tanh[ 2π(z 1500) 2000 ] , which smoothly transitions from the GM-assumed R ω = 3 above 1,000 m to the literature-supported R ω = 10 below 2,000 m. The GHP estimates based on this parameterization of R ω exhibit improved agreement with observations in the main thermocline and above, compared to those based on R ω = 10, although both approaches capture the bottomintensified feature of ε. These studies have greatly enriched our knowledge of R ω .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Liang et al (2021) reported an increase in R ω with depth based on observations conducted in the western Pacific, and established a relationship of R ω (z) = 10 z/b , where b = 2,500 m and z represents water depth. Ferris et al (2022) focused on the Drake Passage region and proposed a depth-dependent parameterization of R ω (z) = 6.5 + 3.5 tanh[ 2π(z 1500) 2000 ] , which smoothly transitions from the GM-assumed R ω = 3 above 1,000 m to the literature-supported R ω = 10 below 2,000 m. The GHP estimates based on this parameterization of R ω exhibit improved agreement with observations in the main thermocline and above, compared to those based on R ω = 10, although both approaches capture the bottomintensified feature of ε. These studies have greatly enriched our knowledge of R ω .…”
Section: Introductionmentioning
confidence: 99%
“…Ferris et al. (2022) focused on the Drake Passage region and proposed a depth‐dependent parameterization of Rω(z)=6.5+3.50.25emtanh][2π(z1500)2000 ${R}_{\omega }(z)=6.5+3.5\hspace*{.5em}\mathrm{tanh}\left[\frac{2\pi (z-1500)}{2000}\right]$, which smoothly transitions from the GM‐assumed R ω = 3 above 1,000 m to the literature‐supported R ω = 10 below 2,000 m. The GHP estimates based on this parameterization of R ω exhibit improved agreement with observations in the main thermocline and above, compared to those based on R ω = 10, although both approaches capture the bottom‐intensified feature of ε . These studies have greatly enriched our knowledge of R ω .…”
Section: Introductionmentioning
confidence: 99%